Drummers of the Najd: musical practices from Wādī al-Dawāsir, Saudi Arabia - Urkevich, Lisa (Proceedings of the Seminar for Arabian Studies, 2011)
Today throughout the Arabian Peninsula, especially in the central and eastern areas, traditional musical works known as al-Dawsārī are well known and often included in all-night music parties. This music, which is frame drum oriented and noted for its lively, colourful character, stems from Wādī al-Dawāsir, a fertile region of south central Arabia. Centuries ago African immigrants and slaves who came to the region to help tend the agriculturally rich Wādī, no doubt influenced, if not introduced, many drumming traditions. Through migration, these Dawsārī styles have spread throughout the Kingdom of Saudi Arabia and other Gulf areas. Intertwined with the drums and music, especially among those of long-standing al-Dawāsir tribal heritage, is also the concept of fighting and competition. Drums were used in battle, blood from the dead was rubbed on them, and women, even though they may be celebrating at an event, would — and will — dance aggressively and competitively to Dawsārī drum rhythms. In the same way that Dawsārī music can incite a lively competitive state, it can also be used to rouse an altered condition, as seen in possessed dancers at late-night parties.